ENTREPRENEURIAL COMPETENCIES REQUIRED BY BUSINESS EDUCATION GRADUATES FOR SUCCESSFUL ENTREPRENEURIAL DEVELOPMENT - OBIDILE, Jacinta Ifeoma; ONYENEKE, Euphemia Nkiruka (Covenant Journal of Entrepreneurship, 2023)
The need for business education graduates and students (would-be-graduates) to integrate properly into the world of work, in the contemporary business world to avert unemployment necessitated the study, to ascertain the entrepreneurial competencies required by business education graduates for successful entrepreneurial development. The study adopted the survey research design. All the business education graduates who were entrepreneurs in the South East geo-political zone of Nigeria constituted the population. Purposive sampling was used to select 187 entrepreneurs (business education graduates) who were managers of their businesses and had existed for five years and above. A structured questionnaire validated by three experts with a reliability coefficient of 0.84 was the instrument for data collection. Data collected were analyzed using Arithmetic mean and Standard deviation for research questions and z-test to test the null hypotheses at 0.05 level of significance. Findings of the study revealed that soft skills such as; analytical thinking, critical thinking, among others and hard skills such as; machine operation, software application, among others, were required by business education graduates for successful entrepreneurial development. The findings also revealed that there is no significant difference in the mean ratings of the respondents on entrepreneurial competencies (soft and hard skills) required for entrepreneurial development as a result of gender. Based on the findings of the study, conclusion was drawn and it was recommended among others that, business education graduates and students should endeavour to imbibe and put into use the identified entrepreneurial competencies for their entrepreneurial development to avert unemployment.